Sabar Implementasinya Dalam Pencegahan Stres - Dra. St. Rahmah, M.Ag (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
Lately, the competition of life began fragmented in specific areas so as to make more stringent way of civilization as happens now makes humans living in it must be able to adjust to developments, technology more sophisticated, the prolonged economic crisis made the economy in society is getting worse, until finally becoming more food shortages. To satisfy all human needs often clash with the level of ability and powerlessness. As a result, people often have psychiatric disorders or stress. Stress can be prevented by blocking various factors that cause stress and shock in a good spirit of the individual factors themselves and the surrounding environment factors are factors in the family environment, school, and community environments. Islam as a source of rules and values against any phenomenon that happens in this world of universal and covers all dimensions of human life both to human problems that are material and psychological (mental) concept offers a patient as a preventive step to cope with the stress.